The Politics of Walmart Moms: Parenthood and Political Attitudes in the 2012 Election. (1st October 2016) - Elder, Laurel; Greene, Steven
ABSTRACT: This research uses 2012 National Election Studies data to explore how parenthood shapes the public opinion of women and men. Our analyses show that being a parent shapes attitudes on issues directly connected to children, such as government funding for education and day care, but also on issues less connected to the day-to-day activities of parenting, including the appropriate role of government and abortion. While the label "Walmart Mom" captures the reality that a large and growing number of mothers are struggling economically, the effect of motherhood, on most issues, holds for all women, regardless of socioeconomic status. This article discusses the implications of our findings concerning the politics of motherhood and fatherhood in light of the changing structure of America's families.